2012
DOI: 10.1111/j.1469-7610.2012.02582.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal executive function, harsh parenting, and child conduct problems

Abstract: Background Maternal executive function and household regulation both are critical aspects of optimal childrearing, but their interplay is not understood. We tested the hypotheses that 1) the link between challenging child conduct problems and harsh parenting would be strongest for mothers with poorer executive function and weakest among those with better executive function, and 2) this mechanism would be further moderated by the degree of household chaos. Methods The socioeconomically diverse sample included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
208
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 203 publications
(227 citation statements)
references
References 40 publications
13
208
3
Order By: Relevance
“…The D–KEFS has considerable research support for its general validity and internal consistency reliability, as well as test–retest reliability across two testing sessions [59]. Consistent with structural findings suggesting that various EF subdimensions load onto a single, common EF factor [60], as well as previous studies using a single, composite EF score (e.g., [61, 62], the 15 standard Achievement scores that emerge from the 8 D–KEFS tests were standardized (i.e., z-scored) and aggregated to form a single EF composite score used in the present study. In the current sample, the internal consistency reliability (i.e., Cronbach’s alpha) and AIC for the composite EF score was .82 and .23, respectively.…”
Section: Methodssupporting
confidence: 56%
“…The D–KEFS has considerable research support for its general validity and internal consistency reliability, as well as test–retest reliability across two testing sessions [59]. Consistent with structural findings suggesting that various EF subdimensions load onto a single, common EF factor [60], as well as previous studies using a single, composite EF score (e.g., [61, 62], the 15 standard Achievement scores that emerge from the 8 D–KEFS tests were standardized (i.e., z-scored) and aggregated to form a single EF composite score used in the present study. In the current sample, the internal consistency reliability (i.e., Cronbach’s alpha) and AIC for the composite EF score was .82 and .23, respectively.…”
Section: Methodssupporting
confidence: 56%
“…One study found that poorer working memory capacity was associated with mothers’ increased negative reactivity toward their child during frustration-based cooperation tasks (Deater-Deckard, Sewell, Petrill, & Thompson, 2010). Notably, following up on this study, poor executive functions more generally were associated with harsh reactive parenting, as well as increased levels of child conduct problems (Deater-Deckard, Wang, Chen, & Bell, 2012). …”
Section: Cognitive Influences On Parental Emotion Regulationmentioning
confidence: 78%
“…Like the first study, the link between higher levels of child problem behaviors and harsher caregiving was present only among mothers with poorer EF (Deater-Deckard et al, 2012). In further analyses, we found that this EF modulating effect essentially disappeared in households that were highly chaotic—lacking in routines, noisy, and crowded.…”
Section: Interpersonal Processesmentioning
confidence: 77%